2018
DOI: 10.1002/marc.201800265
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetal‐Based Combination Therapy for the Treatment of Prostate Cancer

Abstract: The high incidence of prostate carcinogenesis has prompted the search for novel effective treatment approaches. We have employed curcumin (Curc) and diethylstilbestrol (DES) to synthesize a series of polyacetal (PA)-based combination conjugates for prostate cancer (PCa) treatment. Given their bihydroxyl functionalities, Curc and DES molecules were incorporated into a PA mainchain using a one-pot reaction between diols and divinyl ethers. The PA-conjugates released both drugs under acidic conditions, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…[ 125 ] We developed this strategy into a synergistic combinatorial treatment approach by creating a polyacetal conjugate of DES and the anti‐tumor agent curcumin at an optimized ratio that displayed potent anti‐tumor effects. [ 126 ]…”
Section: Nanomedicines For Advanced Prostate Cancer Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 125 ] We developed this strategy into a synergistic combinatorial treatment approach by creating a polyacetal conjugate of DES and the anti‐tumor agent curcumin at an optimized ratio that displayed potent anti‐tumor effects. [ 126 ]…”
Section: Nanomedicines For Advanced Prostate Cancer Treatmentmentioning
confidence: 99%
“…[125] We developed this strategy into a synergistic combinatorial treatment approach by creating a polyacetal conjugate of DES and the antitumor agent curcumin at an optimized ratio that displayed potent anti-tumor effects. [126] Further preclinical examples include the development of PLGA nanoparticles loaded with nimesulide, a cyclooxygenase-2 (COX-2) inhibitor that generally presents with poor solubility, [127] and the encapsulation of EGCG in chitosan polysaccharide nanoparticle, which exhibited enhanced anti-tumoral activity and Table 2. Selected examples of passively-targeted nanomedicines for PCa treatment.…”
Section: Passively-targeted Nanomedicines For Prostate Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Recent studies have also revealed the promising application potential of polymer-drug conjugates (PDCs) as combination nanomedicines. [15][16][17][18][19][20][21][22] Compared with separate administration of PTX and GEM, integrated single nanomedicine formulations for co-delivery of PTX and GEM can simplify the cancer treatment process. 23 However, there is a vast difference in hydrophobicity between PTX and GEM.…”
Section: Introductionmentioning
confidence: 99%